2023
DOI: 10.1111/bju.15981
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant immunotherapy in renal cell carcinoma: a systematic review and meta‐analysis

Abstract: Objectives To synthesise available data regarding the disease‐free survival (DFS) benefit of adjuvant immune checkpoint inhibitors (ICIs) for patients with renal cell carcinoma (RCC) and evaluate the overall safety profile of ICIs in this setting. Materials and Methods We utilised PubMed, Embase, and relevant conference proceedings to identify phase III randomised controlled trials comparing adjuvant ICIs vs placebo/observation for RCC. The primary outcome of interest was DFS. Variables for subgroup analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…These findings align closely with those from Laukhtina et al, [5] who reported an HR of 0.88 (95% CI 0.81-0.96) for DFS (TKIs vs placebos, P = .004) and a slightly different HR of 0.93 (95% CI 0.83-1.04) for OS (TKIs vs placebos, P = .23). In our study, the HR for DFS in the IMT group was 0.82 (95% CI 0.71-0.94) (DFS: IMTs vs placebos, P = .004), which slightly varies from Riveros et al [6] who reported an HR of 0.81 (95% CI 0.63-1.05) (DFS: IMTs vs placebos, P = .11). It is important to note that IPD meta-analysis and conventional meta-analysis are distinct methods.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…These findings align closely with those from Laukhtina et al, [5] who reported an HR of 0.88 (95% CI 0.81-0.96) for DFS (TKIs vs placebos, P = .004) and a slightly different HR of 0.93 (95% CI 0.83-1.04) for OS (TKIs vs placebos, P = .23). In our study, the HR for DFS in the IMT group was 0.82 (95% CI 0.71-0.94) (DFS: IMTs vs placebos, P = .004), which slightly varies from Riveros et al [6] who reported an HR of 0.81 (95% CI 0.63-1.05) (DFS: IMTs vs placebos, P = .11). It is important to note that IPD meta-analysis and conventional meta-analysis are distinct methods.…”
Section: Discussioncontrasting
confidence: 59%
“…[42][43][44][45] This meta-analysis is, to the best of our knowledge, the first to reconstruct and analyze DFS and OS curves, evaluating the efficacy of adjuvant IMTs and TKIs in RCC patients. It also [9] Serplulimab + CT PD- [8] Adebrelimab [6] Atezolizumab [7] Durvalumab represents the first comprehensive investigation into the serious AEs commonly associated with these 2 treatment strategies, comparing the incidence of severe AEs and the discontinuation rates due to AEs. Our study demonstrates that both adjuvant IMT and TKI therapies offer a slight benefit in DFS for patients undergoing nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among combination therapies, ipilimumab (anti–CTLA-4) combined with nivolumab (anti–PD-1) is the regimen that appears to be associated with the highest chances of long-term disease control 6,7 . In addition, the recent positive results of the Keynote-564 trial led to FDA approval of pembrolizumab (anti–PD-1) in the adjuvant setting; however, 3 other studies have failed to show similar benefits 8,9 …”
mentioning
confidence: 99%